2012
DOI: 10.1186/1423-0127-19-80
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein induces neuritogenesis in DRG neuronal cultures

Abstract: AbsractBackgroundDaidzein, a phytoestrogen found in isoflavone, is known to exert neurotrophic and neuroprotective effects on the nervous system. Using primary rat dorsal root ganglion (DRG) neuronal cultures, we have examined the potential neurite outgrowth effect of daidzein.MethodsDissociated dorsal root ganglia (DRG) cultures were used to study the signaling mechanism of daidzein-induced neuritogenesis by immunocytochemistry and Western blotting.ResultsIn response to daidzein treatment, DRG neurons showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
(57 reference statements)
2
12
0
Order By: Relevance
“…Our findings concur with previous observations that puerarin protects against learning and memory in overiectomized (Ovx) mice, and that the beneficial effects of puerarin on improving memory behavior of Ovx mice are associated with synaptic structural modifications, which include an increase in postsynaptic protein PSD-95 content in Ovx mice following puerarin treatment (Xu and Zhang, 2007). Furthermore, several cellular experimental findings (Yang et al, 2012;Zhao et al, 2015) suggesting neuritogenesis, induced by puerarin and related small molecule compounds like daidzein, could be a general mechanism underlying the neurotrophic application are in good agreement to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings concur with previous observations that puerarin protects against learning and memory in overiectomized (Ovx) mice, and that the beneficial effects of puerarin on improving memory behavior of Ovx mice are associated with synaptic structural modifications, which include an increase in postsynaptic protein PSD-95 content in Ovx mice following puerarin treatment (Xu and Zhang, 2007). Furthermore, several cellular experimental findings (Yang et al, 2012;Zhao et al, 2015) suggesting neuritogenesis, induced by puerarin and related small molecule compounds like daidzein, could be a general mechanism underlying the neurotrophic application are in good agreement to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Natural products are increasingly recognized for the promotion of neuronal survival and neurogenesis against neuronal injury and chronic neurodegeneration . Isoflavones including daidzein and genistein are commonly classified as phytoestrogens with the potential to enhance NGF‐induced neurite outgrowth, although the underlying mechanisms remain elusive . After assaying puerarin, daidzein, genistein, calycosin, onion, and naringin in parallel, we found that puerarin, daidzein, and genistein could similarly potentiate NGF‐induced neurite outgrowth (Figure ).…”
Section: Discussionmentioning
confidence: 93%
“…Isoflavonoids also have demonstrated prominent neuroprotective effects against cerebrovascular disorders, hypertension, or PD in rats or cell models [6466]. One of its most abundant isoflavonoids, daidzein [67, 68], exerts neuroprotective effect to enhance neuronal survival and has been implicated to be a potential drug for neurodegenerative diseases [6971]. Treatment with daidzein in PC12 cells reduced A β aggregates and the neuronal cytotoxicity of A β [69].…”
Section: Discussionmentioning
confidence: 99%